Sex Specific Outcomes With Cardiac Resynchronization Therapy in Patients With Symptomatic Heart Failure Having Reduced Left Ventricular Ejection Fraction: A Systematic Review and Meta-Analysis - Muhammad Hamayal, MBBS; Muhammad Arham Abbas, MBBS; Momina Hafeez, MBBS; Saira Mahmud, MBBS; Warda Shahid, MBBS; Saman Naeem, MBBS; Hasan Shaukat Abbasi, MBBS; Muhammad Danyal Tahir, MBBS; Aleea Abbas, MBBS; Iqra Iftikhar, MBBS; Naaemah Saleem, MBBS (American Journal of Medicine Open)
Cardiac resynchronization therapy (CRT) has emerged instrumental in managing heart failure. Notably, there is a lack of evidence of CRT efficacy among both sexes. Thus, this meta-analysis focuses on the long-term benefits of CRT in both sexes. PubMed, The Cochrane Library and clinicaltrials.gov were searched for articles from 2010 to 2024. ROB2 was used to assess risk of bias of RCTs. Newcastle Ottawa Scale was used for quality appraisal of cohorts. Meta-analysis was conducted on Revman 5.4. Out of 2722 articles, only 9 RCTs and 18 cohorts were included. Our results demonstrated that females had a significantly lower risk of composite outcomes compared to males in both RCTs (RR 0.80; 95% CI [0.68, 0.94], P = .006) and cohorts (RR 0.76; 95% CI [0.63, 0.92], P = .004). Results were similar for all-cause mortality. For heart failure hospitalization, only cohorts showed a significant lesser risk in females (RR 0.78; 95% CI [0.65, 0.93], P = .006). Left ventricular ejection fraction improved significantly in females but no differences were observed for NYHA class improvement. Males showed a 31% lower survival rate. However future trials are needed to highlight this variation.